Glutamatergic synaptic input to glioma cells drives brain tumour progression - Venkataramani, Varun; Tanev, Dimitar Ivanov; Strahle, Christopher; Studier-Fischer, Alexander; Fankhauser, Laura; Keßler, Tobias; Körber, Christoph; Kardorff, Markus; Ratliff, Miriam; Xie, Ruifan; Horstmann, Heinz; Messer, Mirko; et al. (Nature, 2019)
Neurons form glutamatergic synapses with glioma cells in mice and humans, and inhibition of AMPA receptors reduces glioma cell invasion and growth.